ANALISIS LITERATUR TENTANG PENGARUH KUALITAS TATA KELOLA SEKOLAH TERHADAP CAPAIAN BELAJAR SISWA SEKOLAH DASAR - Yola Junita; Felisa Jeniari; Rijalul Qadri; Rizki Ananda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to systematically examine the relationship between school governance andstudent learning outcomes in primary education through a literature review approach. Effectiveschool governance is a key element in creating a conducive learning environment, which in turnleads to improved student academic achievement. This study reviewed 20 scientific articlespublished in indexed national and international journals between 2013 and 2024. The resultsshow that the quality of the principal's leadership, the involvement of stakeholders such asteachers, parents and the community, as well as transparency and accountability in schoolmanagement have a direct and indirect influence on student learning outcomes. Theimplementation of school-based management (SBM) was also found to strengthen theindependence and effectiveness of decision-making at the school level. This finding confirms theimportance of increasing the managerial capacity of school principals, strengthening communityparticipation and applying good governance principles in the implementation of basic education.This study recommends the need for affirmative policies to strengthen governance indisadvantaged areas and the need for further field-based research to deepen the understandingof the dynamics of school management and its impact on learning quality.